1952
DOI: 10.1002/jsfa.2740030906
|View full text |Cite
|
Sign up to set email alerts
|

The lignin fraction of animal feeding‐stuffs. II—Investigation of lignin determination procedures and development of a method for ‘acid‐insoluble lignin’

Abstract: Examination of humin residues obtained a t various stages during lignin determination and of the alcohol-soluble fraction of pre-treated food materials has indicated the necessity for modifying the procedures used in lignin determination. Factors affecting the dispersion and hydrolysis of cellulose are reported, and it is shown that in order t o determine as lignin only material insoluble in concentrated acid it is necessary t o filter without dilution after the main treatment. A method for determining ' acid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1954
1954
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Furfurals produce pseudo-lignin when they react with proteins (29) . Earlier nutritional studies regarded the precipitate found on dilution and heating in the KL procedure as nonlignin matter (4,30) .…”
Section: Discussionmentioning
confidence: 99%
“…Furfurals produce pseudo-lignin when they react with proteins (29) . Earlier nutritional studies regarded the precipitate found on dilution and heating in the KL procedure as nonlignin matter (4,30) .…”
Section: Discussionmentioning
confidence: 99%